2013
DOI: 10.2478/pcssr-2013-0020
|View full text |Cite
|
Sign up to set email alerts
|

Cheating is the Name of the Game - Conventional Cheating Arguments Fail to Articulate Moral Responses to Doping

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The instrumental use of banned performance enhancing substances in competitive sport (WADA, 2015) has attracted attention from sport psychology researchers wishing to understand the phenomenon of doping . Doping is viewed as a moral issue by both athletes (e.g., Erickson, McKenna, & Backhouse, 2015) and academics (e.g., Atry, Hansson, & Kihlbom, 2013;Corlett, 2013;Corlett, Brown, & Kirkland, 2013). However, some academics have argued that doping does not violate the spirit of sport (e.g., Savulescu, Creaney, & Vondy, 2013), and reported that sportspersonship does not predict doping (e.g., Barkoukis, Lazuras, Tsorbatzoudis, & Rodafinos, 2011; cf.…”
Section: The Effects Of Moral Disengagement Mechanisms On Doping Likementioning
confidence: 99%
“…The instrumental use of banned performance enhancing substances in competitive sport (WADA, 2015) has attracted attention from sport psychology researchers wishing to understand the phenomenon of doping . Doping is viewed as a moral issue by both athletes (e.g., Erickson, McKenna, & Backhouse, 2015) and academics (e.g., Atry, Hansson, & Kihlbom, 2013;Corlett, 2013;Corlett, Brown, & Kirkland, 2013). However, some academics have argued that doping does not violate the spirit of sport (e.g., Savulescu, Creaney, & Vondy, 2013), and reported that sportspersonship does not predict doping (e.g., Barkoukis, Lazuras, Tsorbatzoudis, & Rodafinos, 2011; cf.…”
Section: The Effects Of Moral Disengagement Mechanisms On Doping Likementioning
confidence: 99%